If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 90 + 7x + -10 + 2x + 10 = 180 Reorder the terms: 90 + -10 + 10 + 7x + 2x = 180 Combine like terms: 90 + -10 = 80 80 + 10 + 7x + 2x = 180 Combine like terms: 80 + 10 = 90 90 + 7x + 2x = 180 Combine like terms: 7x + 2x = 9x 90 + 9x = 180 Solving 90 + 9x = 180 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-90' to each side of the equation. 90 + -90 + 9x = 180 + -90 Combine like terms: 90 + -90 = 0 0 + 9x = 180 + -90 9x = 180 + -90 Combine like terms: 180 + -90 = 90 9x = 90 Divide each side by '9'. x = 10 Simplifying x = 10
| m-11/2=-5/4 | | 7=4z-(2z+1) | | 6=-3(x) | | 10x+9=109 | | 9*9=81 | | 4x-6(3-x)=13 | | 1.5x+.5=-1.0 | | 14*2=x | | 2-1=1 | | -5x-13=7 | | 2+4x=55 | | 3x+2=2(x+6) | | 2r-6(-10+r)=-7 | | 72-4x=5x+21 | | 7-2s+5s+8=13s+25-5s | | 5*2*(-4)+3*6= | | 20-x=-0.68*(20+x) | | x(x+8)-8(x+8)= | | 32-4=3x-26 | | 6x^2-60x+126= | | -3y+5y-4=-7+4y | | 6x^3+29x^2+27x-20=0 | | x^2+(k-1)x+4=0 | | -3h-1=11 | | 4x^2-x+11=0 | | 2x^4-4x^3+2x^2+2x= | | 2x^2-x+1=x^2-4x-1 | | 2+d=4d-2 | | 119-2x=25x+17 | | -3(x+4)=27 | | 6x-24=7 | | (x-2+i)(x-2-i)(x+3)=0 |